Technology-Based Future Science Education: Axiological Philosophy in the Framework of Bibliometric Analysis - Ahzan, Sukainil; Prayogi, Saiful; Azmi, Irham; Asy’ari, Muhammad; Samsuri, Taufik (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Science education is crucial in developing our understanding of the natural world and enhancing knowledge growth. With rapid advancements in information and communication technology, there is a unique opportunity to transform science education into a more interactive, inclusive, and relevant discipline. However, this evolution prompts philosophical questions, especially concerning axiologyâ€”the study of the value and impact of technology on the future of science education. This research explores the axiological aspects of technology integration in science education through a bibliometric analysis, focusing on how technology-based methods can enrich science learning. A comprehensive literature review reveals that technology is crucial in making science education more accessible, motivating students, facilitating the acquisition of new skills, fostering critical thinking, and boosting student engagement. It highlights the value of incorporating technology into educational practices and how it aligns with axiological considerations in science education. The findings emphasize the need for a deeper philosophical understanding of technology’s role in science education to ensure its ongoing relevance and effectiveness. Looking forward, the integration of technology in science learning promises to advance our knowledge and suggests a fertile area for future research, emphasizing the exploration of innovative technological tools that can further enhance science education for all students.